Strategic Transformation of Public Relations Management in Islamic Boarding Schools in the Digital Age - Totok Sudarmanto; Moh. Asy’ari; Mustapha Almasi (IJIBS, 2025)
In the digital age, public relations (PR) management plays a strategic role in enhancing the competitiveness of Islamic boarding schools through communication innovation and institutional branding. However, many pesantren still rely on conventional communication patterns, resulting in a mismatch between public expectations and institutional capacities. This study aims to analyze the transformation of public relations strategies at Nurul Jihad Islamic Boarding School in responding to digital challenges and increasing institutional competitiveness. Using a qualitative case study approach, data were collected through interviews, documentation, and participatory observation, then analyzed thematically. The results show that PR planning is categorized into routine and incidental programs, emphasizing flexibility and responsiveness. Implementation combines traditional and digital media to maintain cultural values while expanding outreach. Evaluation is carried out collaboratively, involving internal and external stakeholders, and supported by capacity building through Focus Group Discussions. This strategic transformation reflects an adaptive PR model that aligns with the two-way symmetrical communication theory and the PESO model. The study concludes that successful PR transformation requires not only technological adaptation but also human resource development and participatory management. The findings contribute to strengthening the institutional image and competitiveness of Islamic boarding schools in an increasingly digitalized educational landscape.